Süleyman Nazif’in hadisat gazetesindeki yazıları (21 teşrinievvel 1334 - 31 mart 1335 / 1918 - 1919) (inceleme-metin-dizin) - Öztürk, Yücel (My University, 2014)
Süleyman Nazif, Servet-i Fünun’dan Cumhuriyet’in ilk yıllarına kadarki dönemde yaşayan en etkili yazarlardan biridir. Özellikle düzyazılarındaki kudretli üslubu dikkat çeker. Birçok gazetede yüzlerce makale yazmıştır. Mütareke Dönemi’nde çıkan Hadisat gazetesindeki yazıları dönemin iyi anlaşılması bakımından önemlidir. Bu yazılarında Mütareke yıllarını siyasî, sosyal ve kültürel açılardan ele alır. Dönemin ünlü yazarlarıyla yaşadığı polemiklere yer verir. Ermeni meselesi ve Vilayât-ı Sitte başta olmak üzere o döneme ait birçok güncel sorunu işler. Nazif, olayları değerlendirirken her zaman vatansever bir duruş sergiler. Yazarın Osmanlı Türkçesine hâkimiyeti ve dilindeki sanatkâr tavrı da bu yazılarında kendini gösterir. leyman Nazif, Hadisat, Mütareke Dönemi, gazete yazıları, Osmanlı Türkçesi …

Süleyman Nazif is one of the most influential authors of the period between Servet-i Fünun and the first years of the Turkish Republic. He is especially notable with his mastery in prose. He had written hundreds of articles in various newspapers. His articles appeared in the Armistice Era paper of Hadisat are of crucial importance in understanding the era. In these articles he accounts the Armistice years in terms of political,social and cultural affairs and he also includes his polemics with the prominent authors of the time. He also elaborates on several matters such as the Armenian Conflict and the Six Vilayets( Vilayat-ı Sitte ). Nazif always had a patriotic approach to matters he wrote on. His writings mentioned above also demonstrate his mastery in Ottoman Turkish and his artistic style in language use. Key Words : Süleyman Nazif, Hadisat, Armistice Era, newspaper articles, Ottoman Turkish…
Keywords: Süleyman Nazif; Tarih ve Eleştiri; Türk edebiyatı